MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN KEPELATIHAN PUSTAKAWAN DI BIDANG TEKNOLOGI DAN INFORMASI - Ferdiansyah, M; Cahyani, Annisa Dwi; Aini, Syafira; Yusuf, Ja'far Maulana; Susanti, Try (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the management of madrasah principals in improving librarian training in the field of information technology. A qualitative approach with a case study design was employed, and data were collected through in-depth interviews with the madrasah principal and librarian. The findings reveal five key aspects: (1) the madrasah principal applies a participatory planning approach, though without a formal training needs analysis mechanism; (2) support is provided through technology infrastructure procurement and motivation, but facilities are not exclusively allocated for the library and no specific budget exists for librarian competency development; (3) training relies on online platforms and external activities with low frequency, with no internally organized training by the madrasah; (4) key constraints include disparities in human resource adaptation to new technologies, infrastructure limitations, and low training frequency that hinder the transfer of training; and (5) evaluation remains observational and based on physical indicators that do not directly reflect improvements in librarian technology competency, with no structured post-training follow-up mechanism. This study recommends adopting a comprehensive evaluation framework such as the CIPP model to build a complete competency development cycle, increasing the frequency of face-to-face training, encouraging librarian competency certification, allocating a dedicated budget for library human resource development, and improving technology facilities to ensure optimal and sustainable implementation of training outcomes.